Left-right asymmetry variation in the pond snail, Lymnaea stagnalis: exploring patterns of gene expression - Johnson, Harriet F. (2016)
The establishment of left-right (LR) asymmetry in animal development remains an unanswered, fundamental question in biology. Many mechanisms of symmetry-breaking have been proposed and supported, although as yet no universal mechanism has been verified across bilaterian animals. Snails provide an invaluable study organism for understanding LR asymmetry, due to the prevalence of chirally variable species. In the pond snail Lymnaea stagnalis LR asymmetry and resulting shell-coiling direction is a well described genetically tractable trait, inherited through a maternal effect. However, the ‘chirality gene’ is still unknown. In L. stagnalis, clockwise (dextral) coiling is the dominant genotype, therefore snails with homozygote genotype ‘DD’ or heterozygote ‘Dd’ both produce dextral offspring, whereas those with the homozygote recessive genotype ‘dd’ have anticlockwise (sinistral) coiling offspring. To further the Davison research group’s ongoing characterisation of the chirality gene in L. stagnalis, this project focussed on gene expression patterns exhibited between chiral genotypes. Differential gene expression was explored via a candidate gene approach, performing quantitative real-time PCR (qPCR) experiments on specific genes of interest, and also a transcriptomic sweep, utilising next generation sequencing. To enable accurate quantification of gene expression by relative qPCR, first, stable endogenous control genes had to be established. In light of general failings of the previously published control genes to meet the criteria for appropriate use of qPCR, five genes were verified for use as stable endogenous controls in L. stagnalis embryo, ovotestis and foot tissue, for the accurate comparison of gene expression between and within chiral genotypes. These endogenous control genes will enable other researchers of L. stagnalis to rapidly identify stable controls for relative qPCR experiments. qPCR experiments were performed to compare gene expression of 13 candidate genes between chiral genotypes in the single-cell embryo, ovotestis and foot tissues. Significant differential expression was observed between chiral genotypes only in the diaphanous related formin gene, Ldia2, and two actin-related protein genes, Larp2/3 1a and Larp2/3 3. A frameshift mutation in the sinistral copy of Ldia2, discovered by the Davison research group, has identified Ldia2 as the primary candidate for the causal gene in LR asymmetry determination in L. stagnalis. In support of this, Ldia2 mRNA was found to be dramatically underrepresented in the sinistral one cell embryo and significantly reduced in the sinistral ovotestis tissue, yet not in the somatic foot tissue. Ldia2 was also the only gene found to be overrepresented in the embryo tissue relative to the ovotestis and foot tissue, providing further support for the functional importance the gene in early development. The expression level of Ldia2 in the heterozygote genotype groups was calculated to be halfway between that of the homozygote groups, indicating equal expression dominance of the alleles at the chirality locus. The expression pattern observed in the actin-related proteins was less clear and will require further analysis to infer any true biological meaning. However due to the close interaction of actin-related proteins and formins the differential expression observed in the embryo tissue provides functional support for the role of Ldia2 in chiral dimorphism. Next generation transcriptome sequencing methods were employed to gain a transcriptome-wide scan of patterns of gene expression in the ovotestis tissue of snails of differing chiral genotype. A comparative analysis was initiated trialling a novel reduced-representation sequencing method, expression RAD sequencing (eRAD) and traditional RNA Seq. eRAD applies the method of restriction-site associated DNA Sequencing (RADSeq) to the transcriptome by utilising double-stranded complementary DNA (cDNA) in place of genomic DNA. Due to delays in sequencing, the RNA Seq data was not received in sufficient time to perform the comparative assessment within this thesis. Consequently, only the eRAD data is presented here. The eRAD data failed to identify reliable differences in gene expression between chiral genotypes, although did provide a transcriptomic resource of de novo assembled contigs, which has been verified through further analyses. Overall the lack of differential expression identified between chiral genotypes in both the qPCR and eRAD analyses has indicated that the sinistral morph of L. stagnalis does not exhibit a large-scale loss of gene function and pleiotropic effects on gene expression. Therefore, the negative consequences of chiral reversal in L. stagnalis, such as the low hatch rate observed in sinistral broods, may all result from the single chirality gene polymorphism.